Synthesis of Unnatural Phosphonosugar Analogues. Issue 6 (12th December 2013) - Dayde, Bénédicte; Pierra, Claire; Gosselin, Gilles; Surleraux, Dominique; Ilagouma, Amadou Tidjani; Laborde, Coralie; Volle, Jean‐Noel; Virieux, David; Pirat, Jean‐Luc
Abstract: The first synthesis of new cyclic phosphonates (phostones), analogues of pentafuranoses containing a phosphorus atom in place of the anomeric carbon in the deoxyribose and deoxyxylose series, is described. Two methods, of respectively six and seven steps, were developed in parallel, and each gave the racemic phosphonosugars in good yields. Compounds analogous to the alpha and beta anomers were isolated and fully characterized by NMR spectroscopy. Abstract : The first synthesis of unnatural phosphono‐analogues of 2‐deoxy ribose and the 2‐deoxyxylose is reported. Two methods, of respectively six and seven steps, were developed in parallel, and each gave the racemic phosphonosugars in good yields. Compounds analogous to the α and β anomers were isolated and fully characterized by NMR spectroscopy.